ALTERATIONS IN HEMATOLOGICAL INDICES IN ANTENATAL AND POSTNATAL MOTHERS WITHIN KERKUK PROVINCE, IRAQ - Azeez, Sarah T.; Bayatli, Feedan J.; Bazzaz, Ayoub; Chelebi, Noorhan A. (PT. Antis International Publisher, 2024)
Background: Variations in some blood indices at antenatal and postnatal periods in Iraqi women are investigated within Kirkuk Province, Iraq. Materials and Methods: The experimental group included 300 pregnant women at third trimester and another 300 postnatal women attended Azadi Hospital, Kirkuk for the period of 12 months compared with 60 control non-pregnant women selected from Kirkuk University students. The blood parameters were analyzed using automated analyzing machine. Results: Hemoglobin (Hb%) had significantly dropped down to (11.83gm/dL±1.04) in comparison with control; however, it significantly (p≤0.022) raised to 12.4gm/dL±1.6) postnatally. Similarly, the packed cell volume (PCV) had significantly (p≤0001-0.03) dropped in pregnant women at antenatal stage to (34.11±7.76%) in comparison with non-pregnant women (37.11±3.33%), but was significantly (p≤0.022) rose, postnatally. Meanwhile, counts of white blood cells (WBC) was significantly (p≤0.001) increased to (11.69x106/dL) in the pregnant than in control (7.42x106/dL); but further rose postnatally to (15.82±4.7x106/dL). Simultaneously, the count of PCV% had significantly (p≤0.037) dropped down in pregnant women (34.11±7.76%) in comparison with their counterparts the control (37.11±3.33%), respectively; but insignificantly rose postnatally, to 36.67±3.8%, and an insignificant decrease was detected in PLT in comparison with their counterparts, the control group, respectively. Conclusion: In almost all healthy pregnant women the hematological indices could normally be altered as a response to nonpathogenic physiological changes in their health status and would soon be recovered, to certain extend, postnatally, though these insights would help in improving health monitoring as well as risk assessment during pregnancy.